A STUDY ON THE ANALYSIS OF CAUSES OF WORK ACCIDENTS IN GRINDING WORKERS USING THE SYSTEMATIC CAUSE ANALYSIS TECHNIQUE (SCAT) METHOD IN SUBCONTRACT X, PT X, NORTH JAKARTA - Agus Joko Susanto; R.Ayu Anggraeni Dyah Purbasari (PT. Jurnal Center Indonesia Publisher, 2025)
Based on data from the HSE department at PT X, North Jakarta, from 2021 to 2024, the highest number of occupational accidents (KAK) occurred among grinding workers, totaling 12 cases. The types of accidents experienced by workers included metal sparks in the eyes, cuts, lacerations, scratches, and first-aid injuries. The purpose of this study is to analyze the causes of occupational accidents among grinding workers at PT X using the Systematic Cause Analysis Technique (SCAT) method. This research is a descriptive-analytic study using observation, interviews, and documentation studies. The research was conducted between July and August 2025. The research population consisted of 32 people, including 30 grinding workers who had experienced accidents, 1 HSE manager, and 1 field coordinator. The sample for this study is the same as the population. Data analysis used univariate analysis and the SCAT method analysis. Based on the results, the most frequent accident experienced by grinding workers was metal sparks in the eyes, involving 30 respondents (100%). The direct causes of these accidents were the use of inadequate PPE by 15 respondents (50%) and the improper use of grinding tools by 11 respondents (36.7%). It is recommended that management commit to maximizing the implementation of established K3 (Occupational Health and Safety) programs and standards so that work-related accidents can be prevented and zero accidents can be achieved.